Strategi Kebijakan PTSL Berbasis Edukasi Partisipatif : Meningkatkan Kesadaran dan Kepatuhan Masyarakat terhadap Hak atas Tanah - Hanafi Hanafi; Aris Sunarya; Sri Roekminiati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Land legality issues remain a persistent agrarian challenge in Indonesia, primarily due to low public awareness and participation in land certification programs. The Complete Systematic Land Registration Program (PTSL) aims to accelerate comprehensive land asset legalization; however, its implementation in Jambi City faces technical, structural, and psychosocial obstacles. This study aims to assess public awareness and compliance regarding land rights, evaluate the effectiveness of participatory education in the PTSL implementation, and formulate a policy strategy aligned with local conditions. A qualitative approach was employed, involving in-depth interviews and field observations with residents, community leaders, and program implementers. The findings reveal that low levels of awareness and compliance stem from limited understanding of the certification benefits, procedural complexity, and distrust rooted in previous bureaucratic experiences. Participatory education plays a vital role in fostering critical awareness and enhancing community engagement. The proposed policy strategies include social mapping, integrated education throughout program stages, participatory incentives, cross-sector collaboration, and community-based monitoring. This study recommends a shift in the PTSL approach from a procedural focus to a community empowerment model to ensure more inclusive and sustainable implementation.